An In Vitro Model of Endemic Burkitt’s Lymphoma (eBL) Pathogenesis; Cooperation of Plasmodium Falciparum and Epstein Barr Virus in DNA Damage Mediated Via Activation Induced Cytidine Deaminase. - Ayivor-Djanie, Reuben (2012)
A Thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirements for the Degree of Master of Philosophy, June-2012